A note on the split common fixed point equality problems in Hilbert spaces - Kilicman, Adem; Mohammed, Lawan Bulama (Institute for Mathematical Research, Universiti Putra Malaysia, 2017)
We study the split common fixed point equality problems (SCFPEP). Furthermore, we formulate and analyse the algorithms for solving this SCFPEP for the finite family of quasi-nonexpansive operators in Hilbert spaces and shows how it unifies and generalizes previously discussed problems. In the end, we give numerical example that illustrates our theoretical results.